Faktor - Faktor yang Mempengaruhi Mahasiswa Tata Rias Universitas Negeri Surabaya pada Profesi MUA - Bintari Putri, Chika Wahyu; Megasari, Dindy Sinta; Nia Kusstianti; Biyan Yesi Wilujeng (Jurnal Tata Rias, 2026)
The purpose of this study was to determine the factors influencing the interest of makeup students at Surabaya State University in choosing the profession of makeup artist and to determine the most dominant factor influencing their interest. This study employed a quantitative approach with an associative approach. The independent variables included social factors, personal factors, psychological factors, and intelligence. The dependent variable was the interest of UNESA makeup students in the profession of makeup artist. Data analysis used the Principal Component Analysis method. The results showed that four main factors influenced the interest of makeup students at Surabaya State University in the makeup artist profession: social factors, personal factors, psychological factors, and intelligence factors. These four factors were interconnected and simultaneously contributed to the formation of student interest. Personal factors were identified as the most dominant factor influencing UNESA makeup students' interest in the profession of makeup artist, contributing 81.863%. Students who have a personal interest or passion in the field of make-up show a greater tendency to consider the profession of Make Up Artist as their career choice.Keywords: interest of students, makeup artist